PERBANDINGAN ERECTION RANGKA BAJA JEMBATAN DENGAN MENGGUNAKAN MAST CRANE DAN TOWER CRANE PADA PROYEK JEMBATAN TRISULA BLITAR - Agnes Hanna Patty, Armin Naibaho, Singgih Fitra Utama, (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2014)
At Trisula bridge project Blitar, Mast Crane (MC) ?was used for the erection of steel frame bridge while Tower Crane? (TC) was an alternative for the implementation of structure work. The purpose of the study is compare the two? cranes in terms of time and cost. The bridge is of 70 m span; the maximum length of MC can reach is of 3 m and TC is of 40 m. The data of daily, weekly, and monthly report and the 18-week planned S ? Curve were needed to find out the implementation time. The implementation cost was calculated from the setting cost of S ? Curve at IDR 739.883.800,00. Pylon method was ratio of maximum strand force 0,914 for MC and 0,924 for TC.The calculations result in 283,065 hours of MC use at IDR 739.883.800,00. And 161,219 hours of TC use at IDR 1.056.436.000,00.Keywords: comparison, erection, frame.